STUDI DESKRIPTIF ACTIVITY OF DAILY LIVING MEMASAK PENYANDANG TUNANETRA - kustandyah, hersiwi (Jurnal Pendidikan Khusus, 2017)
ABSTRACT For people with visual impairment is not easy in performing daily activities in the field of special cooking because of the obstacles of vision. But not all people with visual impairment experience barriers in doing daily activities in the field of cooking. Based on the problem, the purpose of this study is to describe the cooking knowledge for the blind, the daily activities of the blind people in cooking and the constraints experienced during cooking activities. This research uses qualitative research type, with qualitative descriptive approach. Technique of data collecting by interview and observation. The technique of data validity used is triangulation. The data were analyzed by data reduction, data presentation, and conclusion / verification. The result of this research is that blind people have knowledge in cooking activities in theory and practice by optimizing other senses such as taste, ware and perfection which can still be functional in daily activities.   Keywords: activity of daily living, cooking